The understanding a good choice of colour in poster design for children / Ahmad Waffin Mohamad Saudin and Azlan Zainal - Mohamad Saudin, Ahmad Waffin; Zainal, Azlan (Universiti Teknologi MARA, Perak, 2018)
This paper is about investigating the misuse of colour in poster design for children between aged 4 to 7. This paper reviews what scientific colour that can attract children interest. This paper also explores the relation between colour of poster and children's play behaviour, and how this relation can be utilized by designers to promote design for children. Good poster colour can also catch the eyes that see it. The data will be collected and analyse using a quantitative method. Researcher make a survey by giving different poster colour to the children for intended to investigate their colour chosen. This paper will benefit to graphic designers as guideline to help use the correct colour of the posters for children.